2019
DOI: 10.1101/813741
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cucumber green mottle mosaic virus vector for virus-induced gene silencing in cucurbit plants

Abstract: One sentence summary: A CGMMV-based vector enables gene function 21 studies in cucurbits, an extremely low efficiency species for genetic 22 42 hairpin cDNAs resulted in photobleaching phenotypes in N. benthamiana and 43 cucurbits by PDS silencing. Additional results reflect that silencing of the PDS gene 44 could persist for over two months and the silencing effect of CGMMV-based vectors 45 could be passaged. These results demonstrate that CGMMV vector could serve as a 46 powerful and easy-to-use tool for cha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Most of the DEGs identified in this study were found in the 45 DAP samples, suggesting that watermelon resistance to CGMMV infection in the later stage is more complicated. To validate this speculation, we selected 20 DEGs and analysed their roles in watermelon resistance to CGMMV infection using a CGMMV‐based VIGS vector reported previously (Liu et al, 2020). The results of pV190 VIGS assays for watermelon leaf were consistent with those for fruit except for DnaJ11 (Figures S2, 4 and 5).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Most of the DEGs identified in this study were found in the 45 DAP samples, suggesting that watermelon resistance to CGMMV infection in the later stage is more complicated. To validate this speculation, we selected 20 DEGs and analysed their roles in watermelon resistance to CGMMV infection using a CGMMV‐based VIGS vector reported previously (Liu et al, 2020). The results of pV190 VIGS assays for watermelon leaf were consistent with those for fruit except for DnaJ11 (Figures S2, 4 and 5).…”
Section: Discussionmentioning
confidence: 98%
“…Because watermelon is recalcitrant to genetic transformation, analyses of gene functions in this plant are hindered. To circumvent this obstacle, we decided to investigate the molecular mechanisms controlling CGMMV infection in watermelon fruits through reverse genetics using a CGMMV‐based virus‐induced gene silencing (VIGS) pV190 vector as described previously (Lange et al, 2013; Liu et al, 2020). Currently, two VIGS vectors (i.e., the CGMMV‐based pV190 vector and a tobacco rattle virus [TRV]‐based vector) have been reported to be effective in gene silencing in cucurbits (Fang et al, 2021; Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although successful and highly efficient transformation systems have been established in some species, transformation remains the bottleneck in the production of transgenic and genome-edited plants for watermelon as well as many other horticultural species. Transient expression methods, such as virus-induced gene silencing using virus vectors and protoplast-based transient expression assays, have recently been established in watermelon (Igarashi et al, 2009, Tian et al, 2017, Liu et al, 2020, Wang et al, 2021a, and these methods can be applied to study gene functions. However, stable transformation protocols are still the foundation for the genetic engineering of crop traits.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in transient transformation facilitates rapid and efficient understanding of gene function. One of this transient expression strategies is the so called virus-induced gene silencing (VIGS) (Liu et al, 2019).…”
Section: The Family Cucurbitaceaementioning
confidence: 99%